KERJASAMA ORANG TUA DAN GURU DALAM PEMBELAJARAN PAUD DI MASA PANDEMI COVID-19 - Ruat Diana; I Putu Ayub Darmawan; Elsi Susanti Br Simamora (Sekolah Tinggi Teologi Ekumene Jakarta., 2021)
The pandemic has impacted education, so efforts have been made to make education run well. Schools attempt to solve this problem in several ways. One of them is building collaboration between teachers and parents. The research aims to find the collaboration of parents and teachers in carrying out learning in early childhood education during the Covid-19 pandemic. The research was conducted at Kana Ungaran Integrated Early Childhood Education, which was also affected by the Covid-19 pandemic. The author collects data through interviews with teachers and parents. The results showed that the collaboration was carried out by building communication using social media, holding limited meetings, and parenting programs. In this collaboration, parents have a part, namely being a mediator by taking lesson materials to school and guiding children in learning from home. The part of the teacher in this collaboration is to regulate the provision of teaching materials and build communication with parents. Meanwhile, the school plays a role in helping solve learning problems through parental assistance and a visit home program.